2016
DOI: 10.1038/ismej.2016.4
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial communities from Arctic seasonal sea ice are more compositionally variable than those from multi-year sea ice

Abstract: Arctic sea ice can be classified into two types: seasonal ice (first-year ice, FYI) and multi-year ice (MYI). Despite striking differences in the physical and chemical characteristics of FYI and MYI, and the key role sea ice bacteria play in biogeochemical cycles of the Arctic Ocean, there are a limited number of studies comparing the bacterial communities from these two ice types. Here, we compare the membership and composition of bacterial communities from FYI and MYI sampled north of Ellesmere Island, Canad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 65 publications
2
15
0
Order By: Relevance
“…There is mounting evidence that MYI is a unique and important component of the Arctic sea ice system and has a more important ecological role than was previously assumed. For instance, Hatam, Lange, Beckers, Haas, and Lanoil () suggested that a shift from a predominantly MYI to predominantly FYI sea ice cover will result in more functional instability within sea ice bacterial communities with potential consequences for nutrient dynamics in the Arctic marine environment. Furthermore, within the central Arctic Ocean during summer, regions dominated by MYI showed the highest proportion of ice‐related primary production compared to the water column (Fernández‐Méndez et al., ; Gosselin, Levasseur, Wheeler, Horner, & Booth, ).…”
Section: Introductionmentioning
confidence: 99%
“…There is mounting evidence that MYI is a unique and important component of the Arctic sea ice system and has a more important ecological role than was previously assumed. For instance, Hatam, Lange, Beckers, Haas, and Lanoil () suggested that a shift from a predominantly MYI to predominantly FYI sea ice cover will result in more functional instability within sea ice bacterial communities with potential consequences for nutrient dynamics in the Arctic marine environment. Furthermore, within the central Arctic Ocean during summer, regions dominated by MYI showed the highest proportion of ice‐related primary production compared to the water column (Fernández‐Méndez et al., ; Gosselin, Levasseur, Wheeler, Horner, & Booth, ).…”
Section: Introductionmentioning
confidence: 99%
“…Neither have they been reported as abundant in the more nutrient-rich Arctic shelf LMEs [11,60]. We propose that Actinobacteria and Betaproteobacteria are indicators of melting sea ice as they are generally more abundant in fresh than in marine waters [50,61], and they have been reported in a few studies from the Arctic marginal ice zone in melt ponds, the upper ice layer and surface SW mixed with meltwater [62][63][64][65].…”
Section: Community Structure-bacterial Classesmentioning
confidence: 72%
“…For example, the Chukchi Sea is one of the most productive seas on Earth [67]. Some ice-core studies in the Arctic shelf LMEs report dominance of Gammaproteobacteria [68,69], whereas others report dominance of Alphaproteobacteria [53,70] or more or less equal abundances of Gammaproteobacteria, Alphaproteobacteria and Flavobacteriia [64,70]. This variability seems to be independent of the age of the ice (perennial or annual) and more related to the proximity of land, which strongly influences trophic state.…”
Section: Community Structure-bacterial Classesmentioning
confidence: 99%
“…Amplicon-based sequencing of the taxonomically informative small ribosomal subunit became a standard genetic barcode, which allowed the identification of microbial taxa down to the level of ecotypes. Advancing sequencing technologies are generating more sequence reads at a lower cost, affording high spatial and temporal resolution of microbial (primarily bacterial) communities and subsequent investigation of their connectivity, seasonal successions, and biogeography (e.g., Brown and Bowman 2001;Brinkmeyer et al 2003;Collins et al 2010;Hatam et al 2016;Yergeau et al 2017;Rapp et al 2018). Novel sequencing tools, such as the Nanopore MinION have the potential to be used for in-field sequencing, and have been used in remote polar regions (e.g., Johnson et al 2017), but not yet in sea ice.…”
Section: Advances In Microbial Ecologymentioning
confidence: 99%
“…On the operational taxonomic unit (OTU) level (97% cutoff), there seem to be no endemic species for sea ice in certain ice zones so far (reviewed by Deming and Collins 2017), but further studies focusing on strain variability may find differences. It has been shown that the bacterial OTUs are more variable in seasonal sea ice and more related to temperate communities compared to MYI (Hatam et al 2016). Several bacteria found are known to be psychrophilic (e.g., Feng et al 2014), and a large fraction could be cultured (up to 60%, Junge et al 2002).…”
Section: Bacteriamentioning
confidence: 99%